MENINGKATKAN HASIL BELAJAR HIDROKARBON DENGAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MEDIA BULETIN SISWA KELAS X-6 SMA NEGERI 8 BANJARMASIN - Estiningtyas Kusuma W; Bambang Suharto (Universitas Lambung Mangkurat, 2015)
Abstrak. A research on the use of models Cooperative Integrated Reading and Composition (CIRC)-assisted learning media bulletin on hydrocarbon material. This study aims to improve teacher activity, student activity, learning outcomes (cognitive), and the students' response to the use of media-aided model of CIRC bulletin on learning hydrocarbon material. This study used a research design class action (PTK) with 2 cycles. Each cycle consists of planning, action, observation and evaluation, as well as analysis and reflection. The subjects were students of class X-6 SMAN 8 Banjarmasin the number of 33 people. Research data was collected using the observation sheet activity, achievement test, and questionnaire responses. Data were analyzed with descriptive quantitative and qualitative techniques. The results showed that the application of the model-aided media bulletin CIRC can increase the activity score of 53 teachers from the first cycle to a score of 71.34 in the second cycle with the criteria very well. Student activity also increased from a score of 31.17 in the first cycle to a score of 43.33 in the second cycle with the criteria very well. Mastery of cognitive learning outcomes of students also increased, from 72.70% in the first cycle, and 96.97% in the second cycle. X-6 grade students of SMA Negeri 8 Banjarmasin responded positively to the learning by using a model-aided media bulletin Circ.Keywords : Cooperative Integrated Reading and Composition (CIRC), bulletin, cognitive learning outcomes, hydrocarbon.